Prototype of A Smart Trash Bin for Trash Composting Based on Load Cell HX711 and Ultrasonic Sensor - Joni Welman Simatupang; Abdul Aziz Ar-Rafif (Jurnal Serambi Engineering, 2024)
Waste management is one of serious problems in Indonesia.Based on data from the Ministry of Environment of the Republic of Indonesia states that out of 156 cities/regencies, the amount of waste produced is around 17 tons/year. In Bekasi Regency, in 2021 the amount of waste produced is 1,194 tons. Also, burning and stockpiling in the final disposal site still dominating. This researchaimsto make a Smart Trash Bin forcomposting process. We use Arduino Uno as a microcontroller withUltrasonic Sensor HC-SR04 to detect the distance. We also use the sensor Load Cell HX711 as a waste weighing, where theresults will be displayed onthe LCD and compared with manual scale. For composting, we use POC EM4which is mixed with organic waste to speed up fertilizer production. Therefore,trash that goes into the smart trash bin will be soaked in EM4 liquid and waitingfor 20-30 days to get compostingresults. The accuracy of the weighing average reached 90%, from 10 trialswhereonly once the prototype failed to read it correctly. The compost produced was good. As the current system has its limitations, expanding the capacity of the prototype's scales would augment its waste-handling capabilities